Enhanced surface properties of plain carbon steel using plasma nitriding with austenitic steel cathodic cage. (15th October 2016) - Naeem, M.; Shafiq, M.; Zaka-ul-Islam, M.; Ashiq, A.; Díaz-Guillén, J.C.; Shahzad, M.; Zakaullah, M.
Abstract: Non-alloyed steels are very popular in a wide range of applications due to their low cost, but unfortunately, they are not favorable to surface enhancement by nitriding process because of high brittleness. This problem can be overcome by introducing special alloying elements (such as chromium) on the surface by pre-treatment or admixing of alloys in the bulk, but it is not very cost effective. In this study, plain carbon steel specimens are processed by the cathodic cage plasma nitriding (CCPN) technique using an austenitic stainless steel cathodic cage (CC) having variable diameters (13–21 cm). It is observed that the nitriding process significantly improves the hardness without any pre-treatment or admixing of alloys, which is very useful for industrial applications due to reduced cost and processing time. Also, the corrosion and wear rates are significantly reduced. The results are understood in terms of phase structure, crystalline size and strain using XRD analysis, reactive species emission from the plasma using optical emission spectroscopy and SRIM simulation. Graphical abstract: Highlights: Plain carbon steel is successfully nitrided by cathodic cage technique without any pre-treatment or alloys admixing. Plasma diagnostics show a good correlation with the nitriding results. Cathodic cage diameter significantly influences nitriding efficiency. Wear and corrosion rates are significantly reduced.